2016
DOI: 10.1002/prep.201600021
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Fabrication of Insensitive HMX Particles with Polydopamine Coating

Abstract: The development of a facile method for large scale production of insensitive HMX particles is of great importance for energetic materials, especially for insensitive munitions. Inspired by mussels, HMX particles with a thin, robust, wettable and uniform coating based on the self‐polymerization of dopamine were prepared by one‐step solution stirring processes in the study. The as‐prepared HMX@PDA particles showed stable shape, size, and polymorphy compared with original HMX particles. With PDA (polydopamine) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…Hereby, PDA could simultaneously provide strong chemical adhesion and high rigidity and is favorable to coat the TATB crystals in order to reduce irreversible expansion. Recently, the in situ polymerization of dopamine was introduced to coat energetic organic crystals through a simple immersion method . It has been found that the compact and rigid PDA coating is significant for inhibition of phase transition, protection of energetic crystals against thermal damage, and decreasing sensitivity of HMX after heating .…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hereby, PDA could simultaneously provide strong chemical adhesion and high rigidity and is favorable to coat the TATB crystals in order to reduce irreversible expansion. Recently, the in situ polymerization of dopamine was introduced to coat energetic organic crystals through a simple immersion method . It has been found that the compact and rigid PDA coating is significant for inhibition of phase transition, protection of energetic crystals against thermal damage, and decreasing sensitivity of HMX after heating .…”
Section: Introductionsupporting
confidence: 91%
“…Recently, the in situ polymerization of dopamine was introduced to coat energetic organic crystals through a simple immersion method. 26,27 It has been found that the compact and rigid PDA coating is significant for inhibition of phase transition, protection of energetic crystals against thermal damage, and decreasing sensitivity of HMX after heating. 26 However, there is no work, to the author's best knowledge, exploring the application of in situ dopamine polymerization technology on the energetic crystals to control thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The surfaces of the original HMX and HMX@PDA particles were smooth and uniform, as shown in our previous work [14]. The surface morphology of the HMX@PDA@TiO 2 composites was observed by SEM, as shown in Figure 1.…”
Section: Morphology Of the As-prepared Hmx@pda@tio 2 Compositesupporting
confidence: 72%
“…The BET surface area of the composite was 0.96 m 2 g À1 , which is larger than the original HMX and HMX@PDA (the measurement data were shown in our previous work), owing to the nanostructures formed by the TiO 2 nanoparticles on the surfaces. The XRD pattern of the composite confirmed that the 2q values of 14 [28] in the region of 10~608 in Figure 2, which demonstrated that the TiO 2 nanoparticles were deposited on the HMX surface.…”
Section: Structures Of the Hmx@pda@tio 2 Compositesupporting
confidence: 52%
See 1 more Smart Citation